Two new species of oak gall wasps from Turkey (Hymenoptera: Cynipidae, Cynipini) - Mutun, Serap; Dinç, Serdar; Melika, George (Zootaxa, 2020)
Two new species of oak gall wasps, Cynips izzetbaysali sp. nov. and Callirhytis afion sp. nov. (Hymenoptera: Cynipidae: Cynipini) are described from Turkey. The new Cynips species is known only from asexual females and induces detachable leaf galls on Quercus infectoria. The sexual generation of the new Callirhytis species is known to induce acorn galls on Quercus cerris. Data on the diagnosis, distribution, and biology of the two new species are given.